Teacher self-efficacy in music teaching: an exploratory study in Chile - Karla Valdebenito; Alejandro Almonacid-Fierro (International Journal of Evaluation and Research in Education (IJERE), 2026)
Teaching music in primary education is frequently assigned to generalist teachers despite their limited musical training, which raises important challenges regarding educational quality. This study investigates teacher self-efficacy in music teaching among generalist primary school teachers in Chile, a context that remains underexplored in international research. This study employed a mixed-methods sequential explanatory design. In the quantitative phase, data were collected from 61 generalist teachers using an adapted version of the self-efficacy scale for music teaching. Descriptive statistical analyses were conducted to identify the levels and dimensions of the teachers’ self-efficacy. In the qualitative phase, semi-structured interviews were conducted with eight teachers selected purposively based on high and low self-efficacy scores, and the data were analyzed using content analysis. The results indicate that a high proportion of teachers report low self-efficacy, particularly in instrumental performance and singing, which are closely associated with limited initial training and insufficient institutional support for these subjects. Conversely, teachers with higher self-efficacy demonstrate adaptive strategies, innovation, and active help-seeking behavior. The findings highlight the need to strengthen musical competencies in initial teacher education programmers and enhance institutional support, contributing to improved music teaching practices and informing educational policies in similar contexts.